VIRTUAL LABORATORY AS AN EFFECTIVE SOLUTION DURING DISTANCE EDUCATION - Tiahunova, M. Yu.; Lavryk, V. R. (Systems and Technologies, 2023)
In a world where the pace of change and technology is rapidly accelerating, education is more crucial and relevant than ever before. Recent developments in the education sector have fundamentally changed the paradigm of learning, particularly due to two key events: the COVID-19 pandemic and the onset of the war in Ukraine in 2022. These challenges demand new and innovative solutions in the educational process. Meanwhile, the situation in educational institutions has significantly complicated due to the onset of the war in Ukraine in 2022. Risks for students and educators, associated with being on university campuses during conflict, have increased, raising important questions about how to conduct and teach classes during wartime. A common factor that played a vital role in addressing these issues was the presence of a gadget that is almost ubiquitous: the mobile phone. This device became a bridge between students and educators, enabling the delivery of lectures and practical sessions online even when physical access to the university was restricted. Virtual laboratories emerge as a response to modern challenges in education, providing students with the opportunity to receive quality education amidst constraints and crisis. Virtual laboratories allow students to develop skills and enhance their knowledge without leaving home or a safe location. These innovative solutions support the learning process and contribute to the improvement of educational quality. Thus, virtual computer laboratories are an essential element of the educational space that can guarantee learning and development for students even in the most challenging situations. The paper analyzes the subject area, identifies tasks to be addressed when creating a virtual laboratory, and examines the software for remote laboratory access. Examples of tasks relevant to computer engineering are described, along with general features of tasks suitable for virtual laboratories. The paper develops a structural scheme of a virtual laboratory based on the proposed task directions. The choice of hardware and software components for the virtual laboratory within the university and for remote users is proposed and justified. The paper also outlines and describes the algorithm of the system's functioning as a whole.